Sustainability = Good Design - Stelzer, Kevin (Les ateliers de l'éthique / The Ethics Forum, 2006)
Sustainable design is fundamentally a subset of good design. The description of good design will eventually include criteria for the creation of a healthy environment and energy efficiency. These goals will be achieved by an emergent paradigm of design practice: integration. At every level design interests will come together to facilitate common goals for the creation of a rewarding present and a healthy future. Interdisciplinary design teams will flourish. Inter-accommodating and fluidly communicating political structures will grow. Coalescing social values and economic forces will propel integrated strategies. Unique and innovative solutions will increasingly become the objective. One eventual outcome of this integrated or sustainable design practice will be the development of buildings that produce more energy than they consume.